2018
DOI: 10.1136/vetreccr-2018-000713
|View full text |Cite
|
Sign up to set email alerts
|

Inadvertent intrathecal injection of Gudair vaccine leading to recumbency and ataxia in replacement gimmers: a case of ‘OJD staggers’ in North East England

Abstract: Five of 730 replacement gimmers in a 5000-ewe crossbred flock presented with progressive ataxia and recumbency over a two-week period. On gross postmortem examination, there was spinal cord compression and large fibrogranulomatous masses in the spinal canal of two lambs. Histological examination of one mass and the adjacent tissues revealed chronic active necrotising and granulomatous inflammation with acid-fast bacilli and severe granulomatous osteomyelitis, respectively. PCR of the mass was positive for Myco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Poor vaccine storage practices as found in this study were also observed on dairy farms in the UK 22 23 . Hygiene measures taken around vaccination time were variable, but are of paramount importance when using medicines in terms of contamination of the medicine itself or the administration site, as injection site complications have been reported in sheep 24 . Using disinfectant on the applicator needle during vaccination sessions will inactivate live orf vaccine; the SPC states that ‘prior to first vaccination and each subsequent vaccination session, and at the end of each vaccination session, the applicator should be sterilised’.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Poor vaccine storage practices as found in this study were also observed on dairy farms in the UK 22 23 . Hygiene measures taken around vaccination time were variable, but are of paramount importance when using medicines in terms of contamination of the medicine itself or the administration site, as injection site complications have been reported in sheep 24 . Using disinfectant on the applicator needle during vaccination sessions will inactivate live orf vaccine; the SPC states that ‘prior to first vaccination and each subsequent vaccination session, and at the end of each vaccination session, the applicator should be sterilised’.…”
Section: Discussionsupporting
confidence: 53%
“…22 23 Hygiene measures taken around vaccination time were variable, but are of paramount importance when using medicines in terms of contamination of the medicine itself or the administration site, as injection site complications have been reported in sheep. 24 Using disinfectant on the applicator needle during vaccination sessions will inactivate live orf vaccine; the SPC states that 'prior to irst vaccination and each subsequent vaccination session, and at the end of each vaccination session, the applicator should be sterilised'. This was performed by only 27 per cent of respondents, and 10 per cent of respondents indicated to clean the applicator needle with disinfectant in between animals, which are areas of concern with regard to vaccine eicacy.…”
Section: Discussionmentioning
confidence: 99%